EVALUASI PROGRAM PENDIDIKAN PESANTREN SALAFIYAH - KHAERUDIN KHAERUDIN (Jurnal Evaluasi Pendidikan, 2012)
This study is an evaluative study applying the CIPPO evaluation model which focuses on context evaluation, input, process, product, and impact. The purpose of this study is to find out the implementation of the education system at Salafiyah Islamic Boarding School of Pemalang. The result of evaluation showed quite good in context aspect which covered the legality and the existence of the school in community. Based on input aspect, the study showed that: infrastructure wasvery adequate, 50% of the total teachers graduated from university level or were S1 degree holder, the development of curriculum always referred to the Government Regulation No. 55 Year 2007, the school management was good, the students who met the criteria of school admission were only 60% from the total students, and the level of community’s participation to school was low. Based on process aspect, the teachers’ ability and activity, the students’ involvement in teaching learning process reached good score. Yet, the score on supervision from supervisor was poor. Based on product aspect, the score of students’ graduation was good as 100% of the total students passed the national exam. Based on outcome aspect, the study showed that all the aspects met the criteria, namely (1) 66,13% of alumni continued their study in colleges, and (2) 33,87% of alumni got job mostly as teachers at Al Qur'an Study Center for Kids (TPQ).